Sarcoglottis C.Presl - Chinchilla Alvarado, Isler Fabián (2022)
The genus Sarcoglottis was named in 1827 by Czech botanist Carl Borivoj Presl, a professor at the University of Prague. The name comes from the Greek sarkos, meaning flesh, and glotta, tongue, in reference to the texture and appearance of the labellum. Presl (1827) based the genus on the Andean Sarcoglottis speciosa, the type species of the genus.